2014
DOI: 10.15448/1980-6108.2014.2.16325
|View full text |Cite
|
Sign up to set email alerts
|

Risco nutricional em pacientes adultos e idosos de um hospital do sul do Brasil

Abstract: RESUMOObjetivos: Verificar a prevalência do risco nutricional na admissão hospitalar, utilizando o protocolo Nutrition Risk Screening (NRS 2002) e identificar quais foram os aspectos desse protocolo que mais contribuiram para o escore final. Métodos: Foi realizado um estudo transversal com pacientes adultos e idosos de ambos os sexos, admitidos nos departamentos de internação clínica (exceto maternidade, emergência e unidade de saúde mental) de um hospital da cidade de Farroupilha, Rio Grande do Sul. Os indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Regarding the answers of the initial part of the screening tool, results were similar to those found by Aquino and Philippi 40 , Leonhardt and Paluto 42 and Alvarez-Altamirano et al 28 . Gabbardo and Boscaini 38 found the opposite, and the most prevalent answer was the reduction of food intake in the last week followed by weight loss in the last three months. For Giryes et al 41 the most prevalent answers, in descending order, were critically ill patients, weight loss in the last three months, reduction in food intake in the last week and BMI < 20.5kg/m 2 .…”
Section: Weight Loss In the Last 3 Months Reduction Of Food Intake Inmentioning
confidence: 95%
See 3 more Smart Citations
“…Regarding the answers of the initial part of the screening tool, results were similar to those found by Aquino and Philippi 40 , Leonhardt and Paluto 42 and Alvarez-Altamirano et al 28 . Gabbardo and Boscaini 38 found the opposite, and the most prevalent answer was the reduction of food intake in the last week followed by weight loss in the last three months. For Giryes et al 41 the most prevalent answers, in descending order, were critically ill patients, weight loss in the last three months, reduction in food intake in the last week and BMI < 20.5kg/m 2 .…”
Section: Weight Loss In the Last 3 Months Reduction Of Food Intake Inmentioning
confidence: 95%
“…Similar results were found by Giryes et al 41 and Alvarez-Altamirano et al 28 . On the other hand, Gabbardo and Boscaini 38 found that 81.6% of patients had provided at least one affirmative answer. Regarding the answers of the initial part of the screening tool, results were similar to those found by Aquino and Philippi 40 , Leonhardt and Paluto 42 and Alvarez-Altamirano et al 28 .…”
Section: Weight Loss In the Last 3 Months Reduction Of Food Intake Inmentioning
confidence: 95%
See 2 more Smart Citations